Torsional vibrations of Polar-Class shaftlines: Correlating ice–propeller interaction torque to sea ice thickness. (1st January 2023) - Zambon, Alessandro; Moro, Lorenzo; Kennedy, Allison; Oldford, Dan
Abstract: During ship operations in ice-covered waters, propellers often collide with sea ice pieces. This phenomenon represents a severe hazard that affects the torsional stress state of shafting systems and, ultimately, the ship propulsion system reliability. Classification Societies provide ship designers with design loads and criteria to simulate these events, but there are still uncertainties on the actual characteristics of the impacts that ice-class propellers undergo. This paper presents the results of a research activity that combines experimental measurements and numerical analysis to identify the correlation between ice-induced propeller loads and sea ice conditions. The Canadian Coast Guard (CCG) icebreaker Henry Larsen is considered a case study; we simulate its propulsion shaftline as a lumped-element system and validate this model against full-scale data. A series of numerical simulations to predict the ice-induced impact loads on the propeller was performed by using measured dynamic torque data as the analysis input. Finally, the resulting values were correlated with the ice thickness data acquired while the ship was operating. We compare this ice–propeller torque distribution with the homologous quantities calculated as per the current Polar Class framework. The results show high torque response values even when the ship operates in thin ice. Highlights: Full-scale measurements to acquire shaft vibration data and monitor sea ice conditions are conducted on board a Canadian icebreaker. A numerical model simulating the torsional dynamics of a Polar-Class vessel shaftline is validated against full-scale vibration measures. We outline an algorithm to calculate input excitation variables from experimental response data, using a linear dynamic model. The ice–propeller torque peaks obtained from shaft measurement data are correlated to the average ice thickness during various ice navigation scenarios. This study's findings suggest that a review of the current regulatory recommendations to calculate the design ice–propeller excitation may be needed.